Panorama de los efectos psicosociales relacionados con las víctimas del conflicto armado (2020)
This article of theoretical - methodological review arises within the framework of the teaching project, referring to the pedagogical model for the inclusion of people who were part of the Colombian armed conflict. It is substantially proposed to raise awareness of the devastating effects of this social situation affecting the civilian population without distinction of age, gender and socio-economic status. On the other hand, this writing focuses on the psychological effects associated with armed conflict and the behavioral outcome of the victim in their psychosocial environment, which integrates feelings, moods, and various symptoms that alter the mental balance of the victim disrupt individual and family partner integrality, significantly transforming mental health. In this sense, it is proposed to deepen through the qualitative approach an inconceivable social reality, interpreting with the information of various sources, the integrative elements of psychosocial cutting that integrate the intervention programs for the victims of the armed conflict in Colombia.